RESULTS OF CONSERVATIVE BREAST CANCER TREATMENT WITH PLASTIC SURGERY APPLICATION AT NGHE AN CANCER HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Purpose:We conducted this study to evaluate the results of breast cancer preservation treatment with reconstructive surgery at Nghe An Oncology HospitalMethods: A total of 98 female patients with stage 0, I, or II breast cancer underwent breast-conserving surgery using OPS techniques at Nghệ An Oncology Hospital from January 2019 to December 2023.Results: Average age was 47. Histopathological characteristics: Invasive breast carcinoma of no special type (80.6%).  Luminal A subtype (35,7%) were the majority.Surgical techniques: B-mammoplasty for tumors in the upper outer quadrant had the highest rate (34,7%). Followed by Round block and inverted T-mammoplasty. The percentage of patients who had contralateral breast intervention was 9,2%.Surgical outcomes: Local flap techniques were safe with a low rate of complications, and the majority were mild complications. Oncological and cosmetic outcomes: Local flap techniques offered oncological safety and brought high aesthetic results. In this study: Recurrence and survival: Local recurrence rate: 4,2%. Distant metastasis rate: 5,2%. Median disease-free survival estimated by Kaplan–Meier: 45.4 months. Median overall survival estimated by Kaplan–Meier: 45.6 months.Cosmetic outcomes: 81.1% of patients achieved beautiful and good cosmetic results after 2 years. High levels of breast satisfaction were achieved in most patients.Conclusion: OPS is a new, applicable and effective procedure for patients with early stage breast cancer at Nghe An Oncology Hospital.
Keywords: Breast Oncoplastic Surgery